Elder Abuse: developing integrated responses to the abuse and mistreatment of vulnerable populations - Blundell, Barbara (2017)
Abuse and mistreatment affect human rights across all life stages, yet societal views and responses to it are characteristically targeted to specific vulnerable populations such as older people, women and children in domestic settings, and people with disabilities, though there may be overlap in some areas. It is useful to focus on specific populations in developing targeted responses, as it has been proposed that there are more differences than similarities in areas such as child and elder abuse. However, it has been noted that victims of child abuse are more likely to experience abuse later in life as well. Comparing theoretical and practice approaches, as well as synthesising data across both the lifespan and areas of vulnerability, may be useful in developing a more comprehensive explanation of abuse, mistreatment and violence and lead to new ways of addressing it across the lifespan. There may also be overlapping areas that are not well addressed due to siloed responses, for example, spousal abuse in older couple’s relationships. At heart, elder abuse is a human rights issue; looking at abuse and mistreatment more broadly through this lens may help to link disparate areas of practice in this area and strengthen societal responses.